2021
DOI: 10.3389/fpls.2020.607859
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Strategies for Adaptation to Climate Change in Grapevine Production–A Systematic Review

Abstract: In many areas of the world, maintaining grapevine production will require adaptation to climate change. While rigorous evaluations of adaptation strategies provide decision makers with valuable insights, those that are published often overlook major constraints, ignore local adaptive capacity, and suffer from a compartmentalization of disciplines and scales. The objective of our study was to identify current knowledge of evaluation methods and their limitations, reported in the literature. We reviewed 111 pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(80 citation statements)
references
References 117 publications
0
77
0
3
Order By: Relevance
“…However, researchers are still interested in understanding the behavior of well-known grapevine varieties, such as Cabernet Sauvignon, in different regions such as Spain [201], Israel [202], or China [203]. In this sense, multi-scale and multi-lever approaches to quantify the feasibility and effectiveness of the irrigation practices are required [204].…”
Section: Irrigation In Vineyards: Strategies and Advantagesmentioning
confidence: 99%
“…However, researchers are still interested in understanding the behavior of well-known grapevine varieties, such as Cabernet Sauvignon, in different regions such as Spain [201], Israel [202], or China [203]. In this sense, multi-scale and multi-lever approaches to quantify the feasibility and effectiveness of the irrigation practices are required [204].…”
Section: Irrigation In Vineyards: Strategies and Advantagesmentioning
confidence: 99%
“…Extensive research in tree phenology has demonstrated that the increase in temperature and atmospheric CO 2 levels ultimately influences the number of chill hours required for dormancy breaking and the yield and fruit quality of temperate fruit crops [10,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] (examples are given in Tables 1 and 2). Several studies have evaluated the productivity of temperate fruit crops with the current status of global climate change [4,33,[44][45][46][47][48][49][50][51][52][53]. These studies addressed the various challenges that impact temperate fruit production [4].…”
Section: Climate Change and Temperate Fruit Productivitymentioning
confidence: 99%
“…Research has focused on different phenological stages such as bud swelling, the onset and end of blooming of apple and pear trees [44], as well as the adaptability of fruit crops to climate change conditions [45]. In this regard, an evaluation of various adaptation strategies for grapevines was conducted [46][47][48][49]. The projected impacts of climate change on frost effect for some temperate-zone-grown crops such as almond, avocado, and orange were also studied through evaluating plant requirements of energy and water to mitigate frost damage [50].…”
Section: Climate Change and Temperate Fruit Productivitymentioning
confidence: 99%
“…Many research focalize on the improvement of our understanding of the underlying mechanisms controlling the vine and grape responses to climatic parameters that can appear individually or in combination. QTL analyses to identify key genes involved in the control of the characters studied [ 169 ] and adequate breeding programs or the definition of specific cultural practices are required [ 170 , 171 , 172 ]. Altogether, this information will be relevant to understand grape varietal adaptation to climate changes and to assist vine growers in choosing the best genotypes.…”
Section: Discussionmentioning
confidence: 99%